A review of superhydrophobic and omniphobic membranes as innovative solutions for enhancing water desalination performance through membrane distillation - Suriani Abu Bakar (Tanjung Malim, 2024)
A review of superhydrophobic and omniphobic membranes as innovative solutions for enhancing water desalination performance through membrane distillation by Suriani Abu Bakar